Ethnography in nursing research: an integrative review - Carla Lube de Pinho Chibante carlinha; Fátima Helena do Espírito Santo Fatinha (Universidad de Alicante, 2015)
The aim was to produce a synthesis of the Brazilian scientific production on the use of ethnography in nursing research in the period 2009-2013. This is an integrative review, whose question is, 'How has ethnography been used in nursing research?' The search was carried out in the LILACS database. The research corpus comprised seven articles. At a later date, they were submitted to thematic analysis, and two categories emerged. We observed that culture influences the people's lifestyles, which include their preferences, feelings and the meanings they attribute to their experiences. The appreciation of experience and meanings attributed by the clients in the health/disease process enables to bring the health professional and the client together, in order to practice culturally congruent care. The acknowledgement of the cultural status is essential for integral and significant nursing care, where the ethnographic findings contribute towards providing the description of a local reality.